Melodic Intonation Therapy: Back to Basics for Future Research - Zumbansen, Anna; Peretz, Isabelle; Hébert, Sylvie (Frontiers in Neurology, 2014)
We present a critical review of the literature on melodic intonation therapy (MIT), one of the most formalized treatments used by speech-language therapist in Broca’s aphasia. We suggest basic clarifications to enhance the scientific support of this promising treatment. First, therapeutic protocols using singing as a speech facilitation technique are not necessarily MIT. The goal of MIT is to restore propositional speech. The rationale is that patients can learn a new way to speak through singing by using language-capable regions of the right cerebral hemisphere. Eventually, patients are supposed to use this way of speaking permanently but not to sing overtly. We argue that many treatment programs covered in systematic reviews on MIT’s efficacy do not match MIT’s therapeutic goal and rationale. Critically, we identified two main variations of MIT: the French thérapie mélodique et rythmée (TMR) that trains patients to use singing overtly as a facilitation technique in case of speech struggle and palliative versions of MIT that help patients with the most severe expressive deficits produce a limited set of useful, readymade phrases. Second, we distinguish between the immediate effect of singing on speech production and the long-term effect of the entire program on language recovery. Many results in the MIT literature can be explained by this temporal perspective. Finally, we propose that MIT can be viewed as a treatment of apraxia of speech more than aphasia. This issue should be explored in future experimental studies.